STRUCTURING OF PEDAGOGICAL KNOWLEDGE IN PROCESSES OF TRAINING FUTURE TEACHERS (Pedagogy of Higher and Secondary Education, 2022)
The article covers the issues of correlation between informative and procedural components of pedagogical knowledge in the structure of higher education; its fundamental nature and professional orientation of pedagogical discipline curriculum, modul structures of academic studies and various approaches to future teachers training.